Armed Conflict and Maternal Health Care Utilization : Evidence from the Boko Haram Insurgency in Nigeria - Chukwuma, Adanna (Elsevier, 2021)
Retention in maternal health care is essential to decreasing preventable mortality. By reducing access to care, armed conflicts such as the Boko Haram Insurgency (BHI), contribute to the high maternal mortality rates in Nigeria. While there is a rich literature describing the mechanisms through which conflict affects health care access, studies that estimate the impact of conflict on maternal health care use are sparse and report mixed findings. In this study, we examine the impact of the BHI on maternal care access in Nigeria. We spatially match 52,675 birth records from the Nigeria Demographic and Health Survey (NDHS) with attack locations in the Armed Conflict Location and Event Dataset (ACLED). We define BH conflict area as NDHS clusters with at least five attacks within 3000, 5000 and 10,000 m of BH activity during the study period and employ difference-in-differences methods to examine the effect of the BHI on antenatal care visits, delivery at the health center and delivery by a skilled professional. We find that the BHI reduced the probability of any antenatal care visits, delivery at a health center, and delivery by a skilled health professional. The negative effects of the BHI on maternal health care access extended beyond the Northeastern region, that is the current focus of humanitarian programs. Systematic efforts to identify and address the mechanisms underlying reductions in maternal health care use due to the BHI, and to target the affected populations, are essential to improving maternal health in Nigeria.